2017
DOI: 10.1016/j.jfa.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Norm-attaining functionals need not contain 2-dimensional subspaces

Abstract: G. Godefroy asked whether, on any Banach space, the set of normattaining functionals contains a 2-dimensional linear subspace. We prove that a recent construction due to C.J. Read provides an example of a space which does not have this property.This is done through a study of the relation between the following two sentences where X is a Banach space and Y is a closed subspace of finite codimension in X:We prove that these are equivalent if X is the Read's space.Moreover, we prove that any non-reflexive Banach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…According to Rmoutil's result [25], there exists an infinite-dimensional Banach space X (namely c 0 in the equivalent norm constructed by Read [24]) such that the set NA(X ) ⊂ X *…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Rmoutil's result [25], there exists an infinite-dimensional Banach space X (namely c 0 in the equivalent norm constructed by Read [24]) such that the set NA(X ) ⊂ X *…”
Section: Motivationmentioning
confidence: 99%
“…In this section, we will study the existence of n-dimensional linear subspaces in SNA(M), where M is a pointed metric space and n ∈ N. Our main result from the section states that if M contains at least 2 n points (in particular, if M is infinite), then SNA(M) contains an isometric copy of n 1 (see Theorem 1). This provides a shocking contrast when compared to the classical theory of norm-attaining functionals, where Rmoutil showed that an infinite-dimensional Banach space X introduced by Read satisfies that NA(X , R) has no 2-dimensional subspaces (see [25]). In order to prove our main result in this direction, we need a bit of preparatory work.…”
Section: Finite-dimensional Subspacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Example 2. In [13], an equivalent renorming on the Banach space c 0 of sequences converging to 0 is found in such a way that NA(c 0 ) does not contain any vector subspace of dimension strictly greater than 1.…”
Section: Renormings Concerning Schauder Basesmentioning
confidence: 99%
“…A subset M$M$ of a vector space X$X$ is said to be lineable (resp., κ$\kappa$ ‐lineable , for a cardinal κ$\kappa$) if Mfalse{0false}$M\cup \lbrace 0\rbrace$ contains a vector space of infinite dimension (resp., of dimension κ$\kappa$). Lineability problems have been investigated in several areas of Mathematical Analysis; we refer to, for example, [1, 2, 6, 11–13, 24, 25] for a rather non‐exhaustive list of results. Let us just quote here the seminal result of Gurariy [14] that the set of continuous, nowhere differentiable functions is lineable in Cfalse(false[0,1false]false)$C([0,1])$.…”
Section: Introductionmentioning
confidence: 99%